A new type of double-layer gradient cemented carbides: Preparation and microstructure characterization. (October 2016) - Zhang, Weibin; Du, Yong; Zhou, Peng; Peng, Yingbiao; Li, Na; Xie, Wen
Abstract: Based on thermodynamic calculations and a concept of miscibility gap, a new type of double-layer gradient WC–Co–Ti(C, N)–ZrC cemented carbides is prepared through liquid-phase sintering under vacuum at 1465 °C for 1 h. The core of the prepared cemented carbides consists of WC, (Co) binder phase and miscibility gap (Ti-rich and Zr-rich cubic phases), in addition to the surface layer (WC and Co-rich binder phase) and second layer (WC, binder phase and Ti-rich cubic phase). The prerequisite and mechanism for the formation of double layers have been clarified by means of microstructure characterization and thermodynamic calculations. Graphical abstract: